2007
DOI: 10.1111/j.1365-2672.2007.03277.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lactating rabbit does on the development of the caecal microbial community in the pups they nurture

Abstract: Aims:  To study the effect of microbial community of the rabbit does as influenced by dietary factors, on the development of the gut microbiota of their litters. Methods and Results:  Twenty‐four lactating does were given a diet unsupplemented (NAB) or with 100 ppm of bacitracin (BAC) or tiamulin (TIA) to modify their digestive microbiota. Litters were adjusted to six pups. In Trial 1, four does per diet milked their own six pups. In Trial 2, two does per diet nursed three of their pups and three fostered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
(50 reference statements)
1
21
0
Order By: Relevance
“…Comparing the α-diversity of fecal microbiota among the animals, only that of rabbits showed a low value. In rabbits, the number of OTUs in gut microbiota varies greatly [22,[26][27][28]. Accordingly, in the present study, more OTUs were observed in the gut microbiome of other livestock than in that of the rabbits.…”
Section: Discussionsupporting
confidence: 48%
“…Comparing the α-diversity of fecal microbiota among the animals, only that of rabbits showed a low value. In rabbits, the number of OTUs in gut microbiota varies greatly [22,[26][27][28]. Accordingly, in the present study, more OTUs were observed in the gut microbiome of other livestock than in that of the rabbits.…”
Section: Discussionsupporting
confidence: 48%
“…Many factors are important, including genetics (Benson et al, 2010; Zoetendal et al, 2001) and phylogeny (Ochman et al, 2010) and non-genetic factors, like ecology (Muegge et al, 2011), parental care (Abecia et al, 2007; Kyle & Kyle, 1993) and the environment (Bailey et al, 2010; Godoy-Vitorino et al, 2012). The specific importance of these factors in structuring avian microbiota is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pioneer bacteria can modulate the expression of genes in host epithelial cells, thus creating a favourable habitat for themselves, and can prevent growth of other bacteria that are later introduced into the ecosystem (Hooper and Gordon, 2001). The maternal intestinal microbiota and surroundings are the main source of bacteria colonising the newborn's intestine (Abecia et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, the microbial population of the caecum plays a key role in the host digestive physiology, by both providing with nutrients and acting as a barrier against pathogens and promoting the development of immunity (Forthun-Lamothe and Boullier, 2007). The establishment of caecal microbiota in milking kits is markedly determined by that of the doe (Abecia et al, 2007). This link is highlighted by the fact that 50% of postweaning on-farm mortality occurred in only 14% of the litters (De Blas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%